Single-atom cobalt encapsulated in carbon nanotubes as an effective catalyst for enhancing sulfur conversion in lithium-sulfur batteries - Abd Malek, Emilia; Abdulkareem-Alsultan, G.; Nassar, Nassar Maadh Fawzi; Samawi, Khalida Abaid; Salman, Ekhlas Abd-alkuder; Hasan, Hiba Ali; Mahmoud, Hassaballa M. A.; Mohealdeen, Sura Mohammad (Royal Society of Chemistry, 2024)
The application of single-atom catalysts offers an auspicious resolution to the obstacles introduced by the polysulfide shuttle phenomenon and the sluggish sulfur conversion kinetics in lithium–sulfur batteries (LSBs). This research presents results regarding a sulfur host that demonstrates redox activity and resistance to polymeric sulfur species (PSS). High-curvature carbon nanotubes are utilized in the construction of a single atom CoN4 catalyst through a series of steps including pyrolysis, surface processing, electrostatic adsorption, and polymerization. Undoubtedly, the presence of cobalt (Co) atoms as discrete entities was revealed by X-ray absorption spectroscopy and transmission electron microscopy, as these atoms showed dimensions consistent with the sulfur components on the cathode side. This configuration enables catalytic activity with a remarkable 100% atomic utilization functionality. Furthermore, the DFT calculation of free energy values indicates that the reduction of LiPSs on the carbon nanotube with surface curvature is more advantageous compared to the planar carbon surface. The obtained data suggest that the sulfur cathode, which was fabricated utilizing CoSAC/CNT, demonstrates electrocatalytic capability in the transformation of soluble polysulfides to insoluble Li2S. As a consequence, the detrimental effects of the polysulfide shuttle effect are mitigated. The recently introduced sulfur host in the LSB exhibits consistent performance over 1000 cycles. It sustains a capacity of 990 mA h g−1 at a rate of 1C, with a sulfur loading of 2.0 mg cm−2. An impressive area-specific power of 4.1 mA h cm−2 is achieved with a considerable sulfur loading of 7 mg cm−2. This single-atom cobalt catalyst shows significant potential as a next-generation cathode material for LSBs.